PENERAPAN MODEL QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI PECAHAN KELAS IV SD NEGERI 153 PEKANBARU - Kinanti Oktria; Deprizon; Salman; Raisa Berliana (Jurnal Payung Sekaki : Kajian Keislaman, 2025)
This study aims to improve students’ learning outcomes on the topic of fractions trough the applicationof the Quantum teaching model ini gradeIV at SD Negeri 153 Pekanbaru.The backgroundof this researchis the low student achievement in learning fractions and the lackof varied learning strategies used by teachers. This research is a Clasroom Action Research (CAR) conducted in two cycles. Each cycle consists of planning, implementation, observation and reflection stages. The subjects of this study were 26 fourt-grade student. Data collection techniques included learning outcome test, observation sheets of teacher and student activities, and documentation. The results showed that the application of the Quantum teaching model can improve student learning outcomes. The percentageof mastery learning increased from 65,38% in the pre-actionstage to 75,34% in the first cycle, and reached 85,38% in the second cycle. Students’ learning activities also showed a significant improvement. It can concluded that the Quantum teaching model is effective in improving student learning outcomes in the topic of fractions.